SOME PROPERTIES OF INDUCED COVER FROM FAMILY OF COVERING ROUGH SETS - Nguyễn Đức Thuần (Tạp chí Khoa học Đại học Đà Lạt)
Rough set theory is an efficient and essential tool for dealing with vagueness and granularity in information systems. Covering based rough set theory is proposed as a significant generalization of classical rough sets. It is more general and complex than classical rough set theory, hence there is much need to develop sophisticated structures to characterize covering-based rough sets. In this paper, we studied induced cover from family of covering rough set. Some theoretical results related to the measuring significance of knowledge were obtained and investigated.